Saving lives through technology: Mobile phones and infant mortality - Mensah, Justice Tei; Tafere, Kibrom; Abay, Kibrom A. (World Bank, 2022)
Digital technologies can expand access to health services to underserved populations. This paper leverages mobile network expansion and survey data spanning two decades to study the impact of access to mobile phones on infant mortality in Africa. Using plausibly exogenous variations in lightning intensity and (sub)regional convergence in mobile penetration as instrumental variables for mobile network expansion, the analysis finds that mobile phones significantly reduce infant mortality. A 10 percentage point increase in mobile coverage is associated with a 0.45 percentage point reduction in infant mortality. Improvements in health knowledge and behavior and health care utilization appear to be plausible channels.